ANALISIS MINAT MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN UNIVERSITAS NEGERI MEDAN TERHADAP DUNIA KERJA DI BIDANG PROFESI PENDIDIK - Lovega Ars Putri Br Barus; Rachmat Mulyana (STKIP Subang, 2026)
This study aims to determine the interest of students of the Building Engineering Education Study Program at Universitas Negeri Medan in the world of work, particularly in the teaching profession. This research employed a descriptive quantitative approach. The population consisted of all students of the Building Engineering Education Study Program, class of 2022, who had completed educational courses and participated in the School Field Introduction Program (PLP), totaling 83 students. The sampling technique used was total sampling in which all members of the population were included as research respondents. The research instrument was a questionnaire developed based on indicators of interest in the teaching profession. Instrument validity was tested using the Pearson Product Moment correlation, while reliability was tested using the Cronbach’s Alpha coefficient. Data were analyzed using descriptive quantitative analysis with percentage techniques. The results showed that all questionnaire items were valid and reliable. The data analysis indicated that the interest of Building Engineering Education students at Universitas Negeri Medan in pursuing a career in the teaching profession was categorized as high. These findings suggest that students have positive attitudes and strong tendencies toward choosing the teaching profession as a future career, therefore continuous support from the study program is recommended to strengthen students’ interest and readiness to pursue careers as educators.